2015
DOI: 10.1111/gbb.12184
|View full text |Cite
|
Sign up to set email alerts
|

Neural and behavioral epigenetics; what it is, and what is hype

Abstract: The ability to examine epigenetic mechanisms in the brain has become readily available over the last 20 years. This has led to an explosion of research and interest in neural and behavioral epigenetics. Of particular interest to researchers, and indeed the lay public, is the possibility that epigenetic processes, such as changes in DNA-methylation and histone modification, may provide a biochemical record of environmental effects. This has led to some fascinating insights into how molecular changes in the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Some genetic disorders associated with ASD (eg, Rett syndrome; CHARGE syndrome; 15q duplication; Angelman syndrome; and fragile X syndrome), involve genes that either encode epigenetic regulators or are sensitive to alterations in their epigenetic regulation. 223,224 Because epigenetic modifications can be influenced by environmental factors, such as prenatal maternal exposures and postnatal experience, they represent 1 interface between genes and environment. However, epigenetic modifications are not the only mechanisms by which gene expression is regulated, and epigenetics should not be conflated with the broader category of environmental effects.…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some genetic disorders associated with ASD (eg, Rett syndrome; CHARGE syndrome; 15q duplication; Angelman syndrome; and fragile X syndrome), involve genes that either encode epigenetic regulators or are sensitive to alterations in their epigenetic regulation. 223,224 Because epigenetic modifications can be influenced by environmental factors, such as prenatal maternal exposures and postnatal experience, they represent 1 interface between genes and environment. However, epigenetic modifications are not the only mechanisms by which gene expression is regulated, and epigenetics should not be conflated with the broader category of environmental effects.…”
Section: Epigeneticsmentioning
confidence: 99%
“…However, epigenetic modifications are not the only mechanisms by which gene expression is regulated, and epigenetics should not be conflated with the broader category of environmental effects. 223,225 Currently, the evidence that alteration of gene expression by environmental factors plays a causal role in ASD is very limited. [223][224][225][226][227][228] Investigation of the role of epigenetic and other nongenetic modifications that alter gene activity without changing the DNA sequence is an active area of etiologic research in ASD.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Epigenetic changes may play an important role as mediators of the effects of the intrauterine environment on long-term health outcomes in offspring, including neurodevelopmental deficits, behavior, metabolic disorders, and obesity. [14][15][16][17][18][19][20][21][22] Epigenetic modifications are broadly defined as the mitotically heritable chemical or structural changes to DNA, which are involved in the regulation of gene expression without alteration of the underlying DNA sequence. The most widely studied of the epigenetic modifications is DNA methylation.…”
Section: Introductionmentioning
confidence: 99%
“…We have also bred animals to display traits we believe to represent different addiction risks or symptoms (Noronha et al, 2014). Animal studies have recently shown us that JeanBaptiste Lamarck (1744-1829) was not entirely incorrect and that certain so-called epigenetic biochemical modifications of the genome caused by experience can be transmitted in the germ line to future generations (Isles, 2015). This has laid the final nails in the coffin of Genes versus Environment as mutually exclusive sources of generational influence-genes and environment interact in many ways and at all levels of analysis.…”
Section: Perspectivementioning
confidence: 99%